The Maturing Multiplier: Does Firm Age Matter in the Relationship Between Leverage, Liquidity and Profitability on Firm Value? - Imaniar Zahwa, Tiara; Nurul Innayah, Maulida; Yustina Rahmawati, Ika; Widyaningtyas, Dian (DINASTI RESEARCH, 2025)
This study examines the influence of leverage, liquidity, and profitability on firm value, with firm age analyzed as a moderating factor and company size included as a control variable. The research is conducted on firms within the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Through purposive sampling, 41 companies were selected, producing a total of 151 firm-year observations. The analysis employs the Fixed Effects Regression Model, as identified by preliminary panel data diagnostic tests. The findings indicate that leverage and firm age significantly and positively affect firm value, whereas liquidity and profitability do not exhibit statistically significant impacts. Furthermore, the moderating effect analysis shows that firm age strengthens the positive link between leverage and firm value, does not moderate the relationship between liquidity and firm value, and diminishes the positive effect of profitability.